Quantitative field testing Heterodera glycines from metagenomic DNA samples isolated directly from soil under agronomic production. - Yan Li; Gary W Lawrence; Shien Lu; Clarissa Balbalian; Vincent P Klink (PLoS ONE)
A quantitative PCR procedure targeting the Heterodera glycines ortholog of the Caenorhabditis elegans uncoordinated-78 gene was developed. The procedure estimated the quantity of H. glycines from metagenomic DNA samples isolated directly from field soil under agronomic production. The estimation of H. glycines quantity was determined in soil samples having other soil dwelling plant parasitic nematodes including Hoplolaimus, predatory nematodes including Mononchus, free-living nematodes and biomass. The methodology provides a framework for molecular diagnostics of nematodes from metagenomic DNA isolated directly from field soil.